2016
DOI: 10.1080/01443615.2016.1256966
|View full text |Cite
|
Sign up to set email alerts
|

The effects of IL-1A and IL-6 genes polymorphisms on gene expressions, hormonal and biochemical parameters in polycystic ovary syndrome

Abstract: Polycystic ovary syndrome (PCOS) is a multifactorial disease characterised by chronic inflammation. We aimed to investigate an association between IL-1A and IL-6 gene polymorphisms and both hormonal/biochemical parameters and levels of IL-1A and IL-6. A total of 103 women diagnosed with PCOS according to ESHRE/ASRM criteria were investigated. The patients were divided into two groups as obese and non-obese. IL-1A and IL-6 genes polymorphisms as well as hormonal/biochemical parameters and levels of IL-1A and IL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…PCOS is associated with higher serum levels of IL-6 and other inflammatory cytokines [ 2 , 38 ], which could be associated with increased risk of CVD. Metabolic risk in PCOS could be related to IL-6 gene polymorphism [ 39 ] and the metabolic risk may be modified by lifestyle intervention [ 40 ] and metformin treatment [ 41 ]. More studies are needed regarding the long term effect of lifestyle and medical intervention on CVD risk in PCOS.…”
Section: Discussionmentioning
confidence: 99%
“…PCOS is associated with higher serum levels of IL-6 and other inflammatory cytokines [ 2 , 38 ], which could be associated with increased risk of CVD. Metabolic risk in PCOS could be related to IL-6 gene polymorphism [ 39 ] and the metabolic risk may be modified by lifestyle intervention [ 40 ] and metformin treatment [ 41 ]. More studies are needed regarding the long term effect of lifestyle and medical intervention on CVD risk in PCOS.…”
Section: Discussionmentioning
confidence: 99%
“…The detailed characteristics of the 6 included studies are shown in Table 1 . [ 21 26 ] Four studies were performed in Turkey, [ 21 23 , 25 ] one in Austria, [ 26 ] and another in India. [ 24 ] The frequencies of each genotype and allele, with their HWE values, are presented in Table 2 .…”
Section: Resultsmentioning
confidence: 99%
“…[ 24 ] The frequencies of each genotype and allele, with their HWE values, are presented in Table 2 . The analyzed SNP was within the HWE in 3 studies, [ 23 , 25 , 26 ] whereas in the other 3 studies, the polymorphism was not consistent with the HWE. [ 21 , 22 , 24 ] The NOS results indicated that the studies had scores ranging from 6 to 8, with an average of 6.33, which indicated that the methodological quality of the 6 selected studies was generally reliable (Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…In reproductive biology, IL-1 is thought to alter ovulation, fertilisation, and implantation due to its inflammatory traits [ 236 ]. According to research, the polymorphism rs1800587 (−889C/T) reduces IL-1 gene transcription through altering IL-1α protein expression in ovarian tissue in Caucasian population [ 85 , 86 ]. Moreover, the first association study of the two IL-1β polymorphism rs 16,944 (−511C/T) and rs 1,143,634 (+ 3953 C/T) and PCOS development was conducted by Kolbus et al in Caucasian population but failed to find a correlation.…”
Section: Il-1mentioning
confidence: 99%